Application system and data description of the China Seismo‐Electromagnetic Satellite. Issue 6 (10th December 2018) - Huang, JianPing; Shen, XuHui; Zhang, XueMin; Lu, HengXin; Tan, Qiao; Wang, Qiao; Yan, Rui; Chu, Wei; Yang, YanYan; Liu, DaPeng; Xu, Song
Abstract : The China Seismo‐Electromagnetic Satellite, launched into orbit from Jiuquan Satellite Launch Centre on February 2 nd, 2018, is China's first space satellite dedicated to geophysical exporation. The satellite carries eight scientific payloads including high‐precision magnetometers to detect electromagnetic changes in space, in particular changes associated with global earthquake disasters. In order to encourage and facilitate use by geophysical scientists of data from the satellite's payloads, this paper introduces the application systems developed for the China Seismo‐Electromagnetic Satellite by the Institute of Crustal Dynamics, China Earthquake Administration; these include platform construction, data classification, data storage, data format, and data access and acquisition.